Implementasi Pemenuhan Hak Tersangka Pada Tingkat Pemeriksaan di Polsek Panakkukang - Muhaimin Malaba; Marilang (Alauddin Law Development Journal (ALDEV), 2022)
The rights of suspects are part of Human Rights (HAM). In the criminal justice system, investigators who examine suspects (who should be suspected of committing a criminal act) must position the suspect as a subject of criminal investigation (not an object) based on the principle of presumption of innocence and with all rights that must be fully respected, protected and fulfilled by investigators. for the sake of creating legal certainty (equality before the law). This is what must be understood and guided in every law enforcement for all parties involved in the process of examining criminal acts so that the examination process by means of the inquisitor or inquisitorial system does not recur.